Preoperative anemia and total hospitalization time are the independent factors of preoperative deep venous thromboembolism in Chinese elderly undergoing hip surgery - Long Feng; Longhe Xu; Weixiu Yuan; Zhipeng Xu; Zeguo Feng; Hong Zhang (BMC Anesthesiology, 2020)
Abstract Background This study was designed to explore the prevalence and risk factors of preoperative deep venous thromboembolism (DVT) in Chinese elderly with hip fracture. Methods From January 1, 2012, to December 31, 2018, 273 elderly patients over 70 years old with elective hip surgery were collected from the electronic medical records. Collected data included demographic characteristics, comorbidities, ASA classification, types of previous operations, types of anesthesia, operation time, fracture to operation time, preoperative hemoglobin level, anemia, blood-gas analysis, cardiac function, whether transfusion, preoperative hospitalization, postoperative hospitalization, electrocardiograph, lower limb venous ultrasonography and total hospitalization time. Results In these 273 patients, 15(5.6%) had ultrasonography evidence of DVT in affected limbs before surgery. Three of all patients received an temporary inferior vena cave filter placement preoperatively. Fracture to surgery time, preoperative hemoglobin level, anemia, preoperative hospitalization, pulmonary disease and total hospitalization time were statistically different between DVT group and non-DVT group (P < 0.05 for all). Moreover, preoperative anemia (OR: 0.144, 95%CI: 0.026–0.799, P = 0.027) and total hospitalization time (OR: 1.135; 95%CI: 1.023–1.259, P = 0.017) were the two independent risk factors for preoperative DVT. Conclusion Preoperative anemia and total hospitalization time were independent risk factors for venous DVT in Chinese elderly with hip fracture.